The Role of the PARS Strategy in Enhancing Students’ Reading Comprehension - Irpira Irpira; Hajjah Zulianti; Febriyanti Febriyanti (STKIP PGRI Bandar Lampung, 2025)
This research aimed to improve the reading ability of eleventh-grade students at SMA Negeri 16 Bandar Lampung in the academic year 2024/2025 through the implementation of the PARS (Preview, Ask, Read, Summarize) strategy. The study was conducted using Classroom Action Research (CAR) consisting of two cycles, each comprising planning, acting, observing, and reflecting stages. The research subjects were 34 students from class XI. Data were collected through reading comprehension tests, observation sheets, and field notes. The results show a steady improvement in students’ reading ability and classroom engagement. In cycle I, the average learning activity score is 33.05 and the mean test score is 58.52. In cycle II, the learning activity score increases to 37.52, the mean test score rises to 70.45 meeting the MCC. Therefore, these findings demonstrate that the PARS strategy effectively improves students’ active participation and reading comprehension, and considered an effective instructional strategy.